The legal value of INCOTERM “EXW”, on the purpose of the Provincial Audience of Oviedo, June 27, 2019 - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
INCOTERMS are one of the most used elements in international trade relations since many years ago; their use is so frequent that Spanish jurisprudence has analyzed on several occasions; This is the case of the Order of the Provincial Court of Oviedo, Seventh section, of June 27, 2019, which confirms the decision of the Court that declared the lack of international jurisdiction of the Spanish Courts, understanding that who is responsible for knowing the matter is a the Courts of Meeuwen-Gruitrode (Flanders-Belgium). The appeal is raised against the order issued by the Court of First Instance No. 2 of Gijón, which resolves in an estimated sense the declination raised by the defendant, agreeing to file the case, not for a lack of territorial jurisdiction, as erroneously points out the appeal in its opposition to the appeal, but for a lack of international competence, considering that the knowledge of the case would correspond to the Belgian Courts.